27.5k views
4 votes
The sum of the first two terms of an arit

The sum of the first two terms of an arit-example-1

1 Answer

6 votes

SOLUTION:

We are told that;


\begin{gathered} a+a+d=15 \\ a+2d+a+3d=43 \end{gathered}

Rewriting, we have;


\begin{gathered} 2a+d=15 \\ 2a+5d=43 \end{gathered}

Subtracting the first and second equations, we have;


\begin{gathered} 4d=28 \\ d=7 \end{gathered}

and;


\begin{gathered} 2a+7=15 \\ 2a=8 \\ a=4 \end{gathered}

Thus, the first four terms of the sequence are;


4,11,18,25

User Spamdark
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.